The Growth Model of the Automotive Industry in Türkiye: An Input-Output Analysis via the Hypothetical Extraction Method - Ünal, Emre; Polat, Ali Yavuz; Köse, Nezir (My University, 2024)
Purpose: The objective of this research was to ascertain if the portion of the automotive industry that engages in non-tradable goods or export goods is the principal driving force behind the industry's expansion. The purpose of this paper is to fill the gap by focusing on the automotive industry as its principal area of investigation. Methodology: Productivity growth in the automotive industry was estimated utilizing an innovative hypothetical extraction method (HEM) for both the non-tradable goods sector and the export goods sector. Following that, the weighted multipliers approach is employed to allocate the productivity across the non-tradable goods and export goods of the automotive industry. Findings: The findings indicate that the automotive industry maintains a strategy of development driven by exports. Production targeted for the domestic market is subject to significant limitations. Multinational automobile corporations tend to employ the strategy of exporting. The growth model of the automotive industry is significantly influenced by various institutional elements, including the Customs Union, taxes, and vertical integration. Originality: Although the automotive industry is an essential industry for exports, its growth model has not been comprehensively scrutinized. This study primarily focuses on investigating the growth model of the Turkish automotive industry and the institutional factors that influenced its strategic decisions.
Keywords: Productivity; Automotive Industry; Institutional Economics; Export-Led Growth; HEM